Analisis Pelanggaran Kode Etik Akuntan Publik Pada Audit Laporan Keuangan Di Indonesia - Finsensia Sihaloho, Maria; Nency Lumban Siantar, Maria; Natalina Sitanggang, Rini (Jurnal Ilmiah Neraca : Ekonomi Bisnis, Manajemen, Akuntansi, 2024)
This study aims to analyze violations of the auditor's code of ethics in the financial reporting audit process in Indonesia. The Code of Ethics for the Auditing Profession is intended to protect the integrity, independence, and ability of auditors to provide high-quality audit services in accordance with professional standards. However, various cases of violations indicate serious problems in the implementation of the Code of Ethics. This study uses a qualitative method with a case study approach. The method used in this study is a literature review. The results of the study indicate weak enforcement of the auditor's code of ethics when auditing financial statements and violations of the principles of the accounting profession. The study shows that conflicts of interest, non-compliance with the principle of independence and manipulation of audit reports are the most common violations. The main causes of these violations include customer pressure, financial interests, and weak supervision. This study recommends increasing monitoring of audit performance, strengthening law enforcement, and increasing ethics training for auditors to prevent future violations of the code of ethics.